(untitled) (Journal of Hama University, 2022)
The research conducted at Al-Jammaseh, Tartous in 2013 and 2014 seasons.To estimate the heterosis, genetic interaction pattern, and correlation coefficient for productivity and its components, in order to determine the optimal breeding method to improve these traits, using 8 hybrids in Line × tester fashion. Genotypes were evaluated in randomized block design with 3 replications. The hybrids (L4xT1, L1xT2, L2x T2, L4x T2) showed the highest significant value of heterosis in productivity, and the hybrids (L1xT2, L2x T2, L4x T2) for the average fruit weight. These promising hybrids showed the pattern of superior dominance in these two traits. Also, L4xT1 hybrid only showed heterosis comparison to the best parents who had super-dominance in the number of fruits per plant. L1xT1 hybrid only showed high significant heterosis compared to the mid parents, and incomplete dominance towards the better parent in pericarp fruit thickness trait. The productivity was correlated positively and strongly with high significance (0.95 ***), in terms of average fruit weight. It did not correlate with the number of fruits (0.03NS), while it correlated negatively significantly with the pericarp fruit thickness (-0.73 *).These promising hybrids can be exploited commercially after the critical standard heterosis testing. Bottom line: High-yielding hybrids of tomato should be developed commercially; by selecting parents with high desired genetic variation.